The Impact of Software Piracy on Inclusive Human Development: Evidence from Africa - Simplice Asongu; Antonio R. Andrés (African Governance and Development Institute (AGDI), 2015)
The study examines the effect of software piracy on inclusive human development in 11 African countries for which software piracy data is available for the period 2000-2010. The empirical evidence is based on instrumental variable panel Fixed Effects (FE) and Tobit models in order to control for the unobserved heterogeneity and limited range in the dependent variable. The modeling exercise is based on the inequality adjusted human development (IHDI) and its constituents. The following main findings are established. First, from the FE regressions, software piracy consistently improves the IHDI and its constituents. Within this framework, the positive relationship between inclusive human development and software piracy is driven by all its constituents. Second, for Tobit regressions, the positive relationship between software piracy and inclusive human development is confirmed exclusively in the IHDI and literacy specifications. Within the latter framework, the positive relationship between software piracy and inclusive human is driven fundamentally by the literacy rate. Policy implications are discussed.
Keywords: K42; O34; O38; O47; O57; 330; Software piracy; Human development; Intellectual property rights; Panel data; Instrumental variables